A desoneraç\~ao da folha de pagamentos e sua relaç\~ao com a formalidade no mercado de trabalho - Graziela Ansiliero; Leonardo Alves Rangel; Luis Henrique Paiva; Matheus Stivali; Edvaldo Duarte Barbosa; Fernando Gaiger Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– The employer`s payroll contribution for pension system relief has been one of the most important topic on the debate about social security. Some advocates that the traditional source of funds for pension system tends to undergo a process of erosion.And there are critics, who argue that there is not a direct relationship between tax relief and elevation of formality or wages paid, among others.The main objectives of this work are: to evaluate the rationality of proposals for payroll taxation relief; to check for the fiscal and income distribution short-run impacts of these proposals (as well as suggest what need to occur in the formal labour market to offset this release); and to present the arguments against the current tax relief proposals and compensation through another tribute.One of the conclusions reached is that the impact of release on the level of formality, income, income inequality and social security revenues is controversial. It also concludes that linear release without compensation can be detrimental to pension system fiscal equilibrium. Thus, the proposal of focused release has the advantages of being less costly and still have positive impacts on income inequality.
Keywords: J32; H32; H55; O17; 330; Gewerbesteuer; Soziale Sicherheit; Gesetzliche Rentenversicherung; Brasilien